In difesa dell'ordine sociale e delle istituzioni - Calabro, Vittoria (Acta Histriae, 2007)
The article presents the developments in Sicilian legislation in the 18th and 19th centuries, aiming to contain the frequent phenomena of vagabondage and mendicancy. Starting from the pragmatic sanctions with that objective, the research then focuses on the regulations found in the Code for the Kingdom of the two Sicilies, Second Part - Penal Law from 1819
Keywords: 18./.19.st.; berači; klateži; kulturna zgodovina; Sicilija; zakonodaja